Motivation, Physical Health Status, and Academic Burnout as Predictors of Physical Activity Behavior in Adolescents - Ni Putu Cintya Candrika Gauri; Dahlia, Yolly; Ayu Anulus; Iing; Ni Ketut Sri Sulendri (Jurnal Kesehatan Prima, 2026)
Physical activity is an important health behavior among adolescents; however, the prevalence of adolescents with insufficient physical activity remains high, including in West Nusa Tenggara Province. Physical activity behavior is influenced by various predisposing factors, including motivation, physical health status, and academic burnout. This study aimed to determine the relationship between motivation, physical health status, and academic burnout with physical activity behavior among adolescents at SMAN 1 Mataram. This study employed an analytical observational design with a cross-sectional approach. A total of 310 students were selected using stratified random sampling. Data were collected using the BREQ-2, PAQ-A, PedsQL™ 4.0, and MBI-SS questionnaires. Data analysis was conducted using univariate and bivariate analyses (Spearman’s rank correlation test). The results of the study involving 310 adolescents at SMAN 1 Mataram showed that the majority of respondents had a moderate level of physical activity (65.48%), followed by high (20.32%) and low (14.19%) levels. Most respondents demonstrated motivation ranging from balanced to autonomous, perceived their physical health status as fairly good to very good, and had a moderate level of academic burnout. There was a significant positive relationship between motivation and physical activity behavior (rs = 0.11; p = 0.046), although the strength of the correlation was very weak. Meanwhile, no significant relationship was found between physical health status (rs = 0.08; p = 0.136) or academic burnout (rs = 0.02; p = 0.657) and physical activity behavior. There is a significant relationship between motivation and physical activity behavior; however, there is no significant relationship between physical health status or academic burnout and physical activity behavior among adolescents at SMAN 1 Mataram.